Perspective transformation themes among rural midlife college students: Subtle vs. dramatic changes - Glyna Olson; Kleine Paul (Adult Education Research Conference, 1993)
This perspective-seeking study of ten midlife students in a rural community college environment qualitatively explores life histories, personal meanings of learning/education, and perspective transformation among a scantily researched group. Findings indicate: (1) Life history dictated a devalued view of education, (2) education is valued for its utility, (3) personal change is varied and sometimes left undefined, (4) perspective transformation is feared due to possible cultural alienation, and (5) "trigger" events leading to college entry impede or enable original life goals to be realized.